REKONSTRUKSI PENGATURAN PENGELOLAAN SAMPAH BERKELANJUTAN DENGAN KONSEP EKONOMI SIRKULAR - Widayanti Widayanti; Sri Murni; Mieke Anggraeni Dewi (Fakultas Hukum Universitas 17 Agustus (UNTAG) Semarang, 2024)
The waste problem is becoming an increasingly pressing issue as economic growth increases. With environmental conditions that have become a waste emergency, the waste management system needs to use new and more comprehensive methods. In order to realize sustainable waste management, the circular economy concept exists to offer a holistic approach that emphasizes reduction, reuse, recycling and effective waste management. In the legal context in our country, Undang-Undang No. 18 of 2008 about Waste Management is the main legal basis for regulations governing waste management. This article was written with the intention of attempting a juridical analysis of household waste management and the like by considering the circular economy concept, with a focus on the implications and potential for making related regulations that are in line with Law no. 18 of 2008. Through this approach, researchers will uncover various legal aspects that influence the success and challenges in realizing the formation of sustainable waste management regulations in Indonesia. Using normative and descriptive legal analysis methods, this article discusses various legal provisions relevant to waste management, including regulations regarding waste prevention, reduction, processing and management. Apart from that, this research also explores the basic concept of a circular economy in the context of waste management, as well as the prospects for establishing regulations in waste management practices in Indonesia.